Polymer particles filled with multiple colloidal silica via in situ sol-gel process and their thermal property - Byun H. (2017)
© 2016 IOP Publishing Ltd. The in situ formation of dielectric silica (SiO 2 ) particles was carried out in the presence of temperature-responsive poly(N-isopropylacrylamide) particles. Unlike the typical sol-gel method used to prepare various SiO 2 particles, the highly uniform growth of SiO 2 particles was achieved within the cross-linked polymer particles (i.e., the polymer particles were filled with the SiO 2 particles) simply by utilizing interfacial interactions, including the van der Waals attractive force and hydrogen bonding in nanoscale environments. The structural and morphological features as well as the thermal behaviors of these composites were thoroughly examined by electron microscopes, dynamic light scattering, and thermal analyzers. In particular, the thermal properties of these composites were completely different from the bare polymer, SiO 2 particles, and their mixtures, which clearly suggested the successful incorporation of multiple SiO 2 particles within the cross-linked polymer particles. Similarly, titanium oxide (TiO 2 ) particles were easily embedded within the polymer particle template which exhibited improved overall properties. As a whole, understanding in situ formation of nanoscale inorganic particles within polymer particle templates can allow for designing novel composite materials possessing enhanced chemical and physical properties.